A down syndrome patient diagnosed with transient myeloproliferative disease after presenting with cutaneous findings (Annals of Medical Research, 2021)
Transient myeloproliferative disease (TMD) is among the main hematologic problems seen in neonates with Down syndrome (DS). It is usually self-limiting and results in spontaneous remission within 3 to 6 months. Characteristic signs of TMD are leukocytosis, thrombocytopenia, anemia, hepatosplenomegaly, cutaneous nodules, and increased numbers of circulating blasts. In this article, we present a DS neonate without leukocytosis who was diagnosed as having TMD after a diffuse vesiculopapular eruption on the face, which is a different clinical presentation than other cases in the literature. Our aim is to emphasize the importance of early diagnosis and close multidisciplinary monitoring of these patients.